Blueprint for a sustainable energy partnership for the Americas : project report (The Centre for International Governance Innovation WaterlooCA, 2009)
Identifies opportunities to lay the groundwork for the development of concrete initiatives to address the strategic needs of the Western Hemisphere for a sustainable energy future.
Keywords: ENERGY